Bahasa Madura dan Indonesia sebagai Pengantar Ibadah dan Pelajaran Agama di GKJW Pepantan Paleran - El Adibah, Elisa Dourothun Nafis; Mariska, Renita Bella; Nurhayati, Alfisyah (Fakultas Teologi, Universitas Sanata Dharma, 2024)
Language is a cultural element that every country has with its uniqueness. Madura language is the local language used by the people of Jember, especially Paleran Village. In addition to Madurese, the national language is also used in everyday life. Language has a function as a communication tool to convey information to others. With this, it is interesting that researchers want to study the strategy of using Madurese and Indonesian languages as an introduction to worship and religious lessons at GKJW Pepantan Paleran. There are three formulations of the problem studied, including: First, why Madura and Indonesian are used as an introduction to worship and religious lessons in the Church. Second, how is the strategy of using the Madurese and Indonesian languages as an introduction to worship activities and providing religious lessons in the church?. Third, how to implement Madurese and Indonesian languages as an introduction to worship and and provision of religious lessons in the church. This study uses empirical research methods with a literature study approach based on a descriptive qualitative data approach. The results of the research show that the Madurese language is the daily language of the people of Paleran hamlet. First, the use of the Madura language as an introduction is carried out in Sunday worship activities. The Madurese language is used because it makes it easier to convey the Bible written in Madurese. Second, the use of Indonesian is used for religious learning for children, youth, and adults such as mothers and fathers.AbstrakBahasa merupakan unsur budaya yang dimiliki setiap negara dengan keunikannya. Bahasa madura merupakan bahasa lokal yang digunakan oleh masyarakat Jember, terutama Desa Paleran. Selain bahasa madura, bahasa nasional juga digunakan dalam kehidupan sehari-hari. Bahasa memiliki fungsi sebagai alat komunikasi guna menyampaikan informasi kepada orang lain. Dengan hal ini, menarik peneliti ingin mengkaji strategi penggunaan bahasa madura dan indonesia sebagai pengantar ibadah dan pelajaran agama di GKJW Pepantan Paleran. Terdapat tiga rumusan masalah yang dikaji, diantaranya: Pertama, mengapa bahasa madura dan Indonesia digunakan sebagai pengantar ibadah dan pelajaran agama di Gereja tersebut. Kedua, bagaimana strategi penggunaan bahasa madura dan Indonesia sebagai pengantar dalam kegiatan ibadah dan pemberian pelajaran agama di gereja tersebut. Ketiga, bagaimana implementasi bahasa madura dan Indonesia sebagai pengantar ibadah dan dan pemberian pelajaran agama di gereja tersebut. Pada penelitian ini menggunakan metode penelitian empiris dengan pendekatan studi pustaka berdasarkan pendekatan data kualitatif deskriptif. Hasil penelitian yang diperoleh menunjukkan bahasa madura merupakan bahasa sehari-hari masyarakat dusun Paleran. Pertama, penggunaan bahasa madura sebagai pengantar dilaksanakan pada kegiatan Ibadah hari minggu. Bahasa madura digunakan karena mempermudah dalam menyampaikan Al Kitab yang tertulis bahasa Madura. Kedua, penggunaan bahasa Indonesia dipakai untuk pembelajaran agama bagi kalangan anak-anak, pemuda, kalangan dewasa seperti ibu-ibu dan bapak-bapak.